1998
DOI: 10.1063/1.1148897
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Los Alamos solid-state optical refrigerator

Abstract: Laser-induced cooling of a solid by net anti-Stokes fluorescence, first experimentally demonstrated in 1995, can be the basis of a new type of cryocooler, an optical refrigerator. This article describes the physics and design issues of a practical optical refrigerator for operation at 77 K. In particular, the Los Alamos Solid-State Optical Refrigerator (LASSOR) which we are developing would have an operating efficiency comparable to commercial small cryocoolers, be completely vibration-free and operate for yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Laser cooling of solids can be exploited to achieve an all-solid-state cryocooler [4][5][6] as conceptually depicted in Fig. 2.…”
Section: Basic Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser cooling of solids can be exploited to achieve an all-solid-state cryocooler [4][5][6] as conceptually depicted in Fig. 2.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Although progress is being made, optical refrigerators need to be more efficient and operate at lower temperatures, below about 170 K, to be competitive with other solid-state coolers such as thermoelectric (Peltier) devices. Several studies have shown that ytterbium-or thulium-doped solids should be capable of providing efficient cooling at temperatures well below 100 K [4,27,38]. are measured with thermocouples on the sample and chamber; the internal temperature of the glass is inferred [22].…”
Section: The 4-level Model For Optical Refrigerationmentioning
confidence: 99%
“…On the other hand, an optical cryocooler-like the one described in Refs. [10,11]-would have many advantages: it has no mechanical parts and, thus, there are no vibrations, no noise, and-with the advent of the new generation diode lasers-it would consume very little power. Other important applications of this type of laser cooling are, for example, the development of radiationbalanced laser that use dual wavelength pumping to offset the heat generated by the pump laser.…”
Section: Laser Cooling Of Luminescent Solidsmentioning
confidence: 99%
“…We add for convenience two linear heat transfer laws such as: (28) Due to equations of the model (7,8,16,25), it is easy to conclude that minimum of VI (energy expense), corresponds to Maximum of COPMAF, and Maximum of 1111 , efficiency relative to the second law of Thermodynamics, with the constraint of given useful effect for the machine.…”
Section: Carnot Irreversible Maf With Imposed Useful Effectmentioning
confidence: 99%
“…For example LOS ALAMOS lab developps an optical refrigerating machine said LASSOR ; this machine is operating near 77 K, with ZBLANP materials in which antistokes fluorescence induced by laser produces the useful effect [28].…”
Section: Conclusion -Perspectivesmentioning
confidence: 99%